A Study on Prescription Pattern and Assessment of Smoking as a Risk Factor among COPD Patients in a Tertiary Care Hospital - V, Aiswarya A; C, Suja; M, Krishnapriya; Unni, P V Sruthi; Salim, Safna (Journal of Pharmacy Practice and Community Medicine)
Aim: The aim is to study the prescription pattern and to assess whether smoking is a major risk factor among COPD patients in a tertiary care hospital. Materials and Methods: A prospective observational study was conducted for 6 months. All the data were collected, documented and analysed based on standard protocol. Data collected were entered and statistically analysed using Microsoft Excel. Results: 120 patients (83 male and 37 female) were included in the study. COPD was more common in the age group of 61-70 years with an average age of 66.8 years. Hypertension ((38.33%) was the most common comorbidity followed by diabetes mellitus. Smoking (66.6%) was a major risk factor followed by indoor pollution (16.60%) outdoor pollution, family history and asthma respectively. Among smokers, 61.25% were ex-smokers. 46.25% of smoking patients had pack years of 11-20. Most commonly prescribed drugs were Bronchodilators (98.30%), antibiotics (85.80%) and corticosteroids (70%). Deriphylline was the most commonly prescribed bronchodilator. Beta lactam antibiotics were most commonly prescribed antibiotics. Among other drugs, GI drugs were commonly prescribed. Parenteral route was mostly preferred, followed by inhalation and oral respectively. Conclusion: The study provides insight into the prescription pattern and shows that smoking is a major risk factor among COPD patients. In this study, bronchodilators were the most commonly used drug followed by antibiotics and corticosteroids. Smoking is a major risk factor followed by indoor pollution, outdoor pollution, family history and asthma respectively.
Keywords: Chronic obstructive pulmonary disease; Comorbidities; Prescription pattern; Smoking; Risk factors